Study on antioxidant and antidiabetic properties of phloroglucinol from brown macroalgae Padina australis Hauck - Murugan, Amarchand Chordia (2018)
Diabetes is a metabolic disorder characterized by high levels of blood glucose. It is caused by the pancreatic insufficiency or by insulin resistance. Marine macroalgae extracts have been established to have strong antidiabetic and antioxidant properties. In the present study, the antidiabetic and antioxidant potential of polyphenolic extract from a brown seaweed Padina australis was evaluated. Methanolic (80:20 % of MeOH: Deionized Water v/v) extract of P. australis was partitioned with five different solvents. The carbolytic enzyme inhibiting functions, radical scavenging activity assay against 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), ferrous ion chelating (FIC) activity, beta-carotene bleaching properties are evaluated. The antiradical and antidiabetic inhibition assays were statistically significant as the different extracts of P. australis inhibited the enzymes in vitro and in vivo. Among the five different fractions, n-butanol fraction showed significantly higher antiradical and antidiabetic inhibitory activity. The methanolic extract was subjected to TLC and HPLC analysis to identify the bioactive molecules present in the mixture of extract. Further LC-MS analysis of n-butanol 5th fraction revealed the presence of three Phlorotannin compounds namely Phloroglucinol, Eckol, and Phlorofucofuroeckol A. Sephadex LH-20, column chromatography technique, was employed to isolate Phloroglucinol compound for further study. Phloroglucinol isolated and purified from the active fraction was evaluated for antidiabetic effect in Streptozotocin-induced diabetic rats. Among the tested portions, n-butanol fraction had significant α- glucosidase and α-amylase inhibitory activity with IC50 value 2.06 ± 0.14 and 2.90 ± 0.08 mg/mL respectively, as compared to Acarbose. Acute toxicity of the isolated pure compound at 20 and 40 mg/kg doses in Swiss Albino mice was found to have potent antidiabetic activity by ameliorating glucose, lipids, and antioxidant parameters. The toxicology studies also showed that the pure compound Phloroglucinol did not have any toxic effects in the internal organs; biochemical and hematological parameters. These findings suggest that the dietary use of Padina australis and the isolated compound Phloroglucinol can be used as medicine for the treatment of diabetes. This work could help to develop new oral antihyperglycemic agent in the management of diabetes mellitus.